Frequency‐dependent dynamic behavior of a poroviscoelastic soil layer under cyclic loading. (2nd March 2020) - Chen, Weiyun; Mou, Yumin; Xu, Lingyu; Wang, Zhihua; Luo, Junhui
Summary: In this study, a linear poroviscoelastic model based on the Biot theory is proposed to analyze the dynamic response of partially saturated soil. Both the flow‐dependent and flow‐independent poroviscoelastic behaviors are described in the proposed model. The compressibilities of both the constituents, including the skeleton material and porefluid, are considered, and the effective skeleton stress is determined using the linear viscoelasticity law based on the generalized spring‐dashpot model. The soil surface is subjected to two types of harmonic loading, namely, vertical compressive loading and lateral shear loading. The influences of the relaxation time, saturation degree, and soil permeability on the surface and interior dynamic responses of the soil layer are investigated. It is revealed that the amplification factor, effective stress, and pore pressure decrease as the viscous damping increases, indicating that neglecting the viscoelastic property of solid skeleton could overestimate the induced dynamic responses. Furthermore, in comparison with the viscous damping of the solid skeleton, the viscous coupling involving the viscous resisting forces between the solid skeleton and pore fluid has limited effect on the dynamic behavior of the soil layer.